Support of Family Rewards for Positive Self-Image in Adolescents with Thalassemia - Nur Wulan Agustina; Ratna Agustiningrum; Wahyuni Wahyuni; Maryatun Maryatun (CV. Global Health Science Group, 2022)
Thalassemia is a condition that occurs due to blood disorders that are carried from birth. This condition is characterized by a lack of oxygen-carrying protein in addition to the presence of a number of red blood cells in the body that is less than normal. One form of treatment is a blood transfusion. Continuous blood transfusions can result in physical and psychological problems. Psychological problems that occur include the acceptance of a negative self-image. The purpose of this research is to analyze the support of family self-esteem on self-image thalassemia adolescents. Research using cross sectional approach. The research sample consisted of 30 thalassemia adolescents at PT RSUP Dr. Soeradji Tirtonegoro Klaten which is recorded as routinely carrying out blood transfusions. Data was collected using a questionnaire. Data analysis used the pearson product moment test. The results of the study found that the majority of families provide good family esteem support and most adolescents with thalassemia have a positive self-image. The conclusion of the study is that the better the appreciation support given by the family, the more positive the self-image of adolescents with thalassemia will be.